2018
DOI: 10.1016/j.gca.2018.02.049
|View full text |Cite
|
Sign up to set email alerts
|

On the changing petroleum generation properties of Alum Shale over geological time caused by uranium irradiation

Abstract: An interdisciplinary study was carried out to unravel organic-inorganic interactions caused by the radiogenic decay of uranium in the immature organic-rich Alum Shale (Middle Cambrian-Lower Ordovician). Based on pyrolysis experiments, uranium content is positively correlated with the gas-oil ratios and the aromaticities of both the free hydrocarbons residing in the rock and the pyrolysis products from its kerogen, indicating that irradiation has had a strong influence on organic matter composition overall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 71 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…1e). Focusing only on immature samples (squares), the Alum Shales exhibit highest aromaticity levels, most likely caused by uranium irradiation (Yang et al, 2018), followed by Barnett Shales and lowest for the Posidonia Shales. This directly confirms results of Zhang et al (2012), who reported that sorption capacity decreases in the order Type III Cameo Coal, Type II Woodford Kerogen, Type I Green River Kerogen, and Ziegs et al (2017), who showed for Mandal Fm.…”
Section: Resultsmentioning
confidence: 99%
“…1e). Focusing only on immature samples (squares), the Alum Shales exhibit highest aromaticity levels, most likely caused by uranium irradiation (Yang et al, 2018), followed by Barnett Shales and lowest for the Posidonia Shales. This directly confirms results of Zhang et al (2012), who reported that sorption capacity decreases in the order Type III Cameo Coal, Type II Woodford Kerogen, Type I Green River Kerogen, and Ziegs et al (2017), who showed for Mandal Fm.…”
Section: Resultsmentioning
confidence: 99%
“…A correlation based on a larger sample set showed that the uranium content generally correlates well with pyrolysate composition (Fig. 13) in that U-richer samples generate pyrolysates with higher GOR and higher aromatic compounds content (Yang et al, 2018). In the same publication Fourier Transform Ion Cyclotron Resonance mass spectrometry was used to evidence the alteration of the kerogen structure.…”
Section: Uranium Irradiation Effect On Organic Matter In the Alum Shale Formationmentioning
confidence: 99%
“…Analytical pyrolysis (Horsfield et al, 1992;Lewan and Buchardt, 1989;Yang et al, 2018) suggests a rather gassy petroleum composition throughout the classical oil window development, even for samples which were less affected due to lower uranium content. For example, the PhaseKinetics approach (di Primio and Horsfield, 2006) was applied for one immature, Middle…”
Section: Organic Matter As Source and Reservoir (Gas Storage Capacity)mentioning
confidence: 99%
See 2 more Smart Citations